2018
DOI: 10.1186/s13690-018-0308-y
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of prelacteal feeding practice and its association with place of birth in Ethiopia: a systematic review and meta-analysis, 2017

Abstract: BackgroundPrelacteal feeding is one of the commonest inappropriate child feeding practice which exposes to malnutrition, infection, and neonatal mortality. However, there is no systematic review and meta-analysis that estimates the pooled prevalence of prelacteal feeding and its association with place of birth in Ethiopia. Therefore, this study aimed at investigating the magnitude of prelacteal feeding practice and its association with home delivery in the country.MethodsPrimary studies were accessed through, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 50 publications
6
23
1
Order By: Relevance
“…Berhan district [20], Debre Markos town [21], Bahir Dar City [19], Ethiopia [8]. Those mothers who gave birth at health institutions could get information on the advantage of optimal breastfeeding and disadvantage of prelacteal feeding from health professionals which can result in avoidance of prelacteal feeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Berhan district [20], Debre Markos town [21], Bahir Dar City [19], Ethiopia [8]. Those mothers who gave birth at health institutions could get information on the advantage of optimal breastfeeding and disadvantage of prelacteal feeding from health professionals which can result in avoidance of prelacteal feeding.…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia, 8% of children received prelacteal feeding [7]. Systematic review and meta-analysis on prelacteal feeding practice was conducted in Ethiopia and found a pooled magnitude of prelacteal feeding practice 26.95% but the magnitude in the primary studies were ranging from 6.1%( SNNPs) to 75.8% (Oromo Region) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its harmful effects, prelacteal feeding is a deep rooted common nutritional malpractice that raises global concern. For example, country wise, its prevalence was: Jammu and Kashmir, India (88.0%), Vietnam (73.3%), Nepal (26.5%), western Uganda (31.3%), Nigeria (60.5%), Mansoura, Egypt (58%) and Ethiopia (26.95%) [10][11][12][13][14][15][16]. Moreover, the 2016 Ethiopian Demographic and Health Survey (EDHS) has shown that 25.9% of the neonates were given different prelacteal feeds.…”
Section: Introductionmentioning
confidence: 99%
“…Community based studies conducted at different parts of Ethiopia have shown burden of prelacteal feeding along the spectrum of the national pediatric nutrition system; for instance, in Raya Kobo town (11.1%), Motta town (20.3%), Afar region (42.9%), Harar city (45.4%), Fiche town (24.4%), Aksum town (10.1%), Sidama zone (25.5%) and Debre Markos town (19.1%) [18][19][20][21][22][23][24][25]. Both the global and national studies have shown that common prelacteal foods include plain water [13,22], raw butter [20], sugar (glucose) water, honey, tea and fruit juice [13,16,25]. The pre-lacteal use of these foods was found to be positively associated with many factors like delayed initiation of breast feeding [19][20][21]25], home delivery [16,21,25], cesarean delivery [11,23,25], inability to read and write [12,25], male neonate [25], maternal belief on the purported advantages of prelacteal feeding [23], less than four ANC visits [12,15,21,23], previous experience of prelacteal feeding [25] and influence from somebody else [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation